Hubungan Kekuatan Otot Tungkai Dengan Kecepatan Lari 100 Meter Siswa Kelas XI - Budiyanto, Budiyanto; Febrianti, Riska Ayu; Ladjiku, Akram; Rastini, Rastini; Tahir, Nandar; Umar, Is Suleman; Hidayat, Joni Taufik; Ikhsan, Haerul; Ilham, Al (-, 2025)
This study aims to determine how strong the relationship is between leg muscle strength and 100-meter running speed in class XI students at SMA Negeri 3 Gorontalo. The hypothesis in this study is "There is a relationship between leg muscle strength and 100-meter running speed in class XI students at SMA Negeri 3 Gorontalo." The method used in this study is the experimental method, which follows the steps "Pre Test (X1), Treatment (T), and Post Test (X2). The sample determined for this study consisted of 20 class XI students at SMA Negeri 3 Gorontalo, who were selected by Purposive Sampling. The data obtained showed that r count (0.866) was greater than r table (0.444). So, there is a significant relationship between the independent variable and the dependent variable. The data can prove that there is a relationship between leg muscle strength and 100-meter running speed in class XI students at SMA Negeri 3 Gorontalo.